Association of exercise-related injuries with body composition and aerobic capacity in amateur athletes - Shahzadi Moeeza Humayun; Ambreen Farooq; Amna (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
This study was conducted to evaluate the association of exercise-related injuries with body composition and aerobic capacity in amateur athletes. In this cross-sectional study 374 participants were recruited including both male and female amateur athletes; from Shoaib Akhtar and Abdul Qadir Cricket Academy, Lahore Pakistan. The study duration was four months, from September 2024 to January 2025. The participants of the study were recruited by using a non-probability convenient sampling technique. Participants’ hip and waist dimensions were measured and Cooper’s test assessed their aerobic capacity values. Additionally, responses for injury incidence rate and psychological readiness values were derived from their respective questionnaires. The study showed that males had a slightly higher waist-to-hip ratio (W/H ratio) than females (0.906 versus 0.896), while females showed better aerobic fitness compared to males (Cooper value: 12.89 versus 12.33). Muscle cramps were the most common injury, followed by fractures and concussions. Weak negative correlations were found between injury incidence and both aerobic fitness and W/H ratio. Injury incidence also showed a slight inverse relationship with age. However, no strong relationships were established between BMI, fitness levels, or demographic factors and injury incidence. The study concluded that as the injury incidence rate increases, aerobic capacity decreases. Waist-to-hip ratio and age had a slight inverse relationship with injury incidence rate while BMI and psychological readiness didn’t have a significant correlation with injury incidence rate.